If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cos(2x) + -5cos(x) = 1 Remove parenthesis around (2x) 3cos * 2x + -5cos(x) = 1 Reorder the terms for easier multiplication: 3 * 2cos * x + -5cos(x) = 1 Multiply 3 * 2 6cos * x + -5cos(x) = 1 Multiply cos * x 6cosx + -5cos(x) = 1 Multiply cos * x 6cosx + -5cosx = 1 Combine like terms: 6cosx + -5cosx = 1cosx 1cosx = 1 Solving 1cosx = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '1osx'. c = o-1s-1x-1 Simplifying c = o-1s-1x-1
| -6(-8)-2(-2)16= | | 7+2a=-5(a+6) | | (2x^2+3x+5)+(-x^2+4x-7)= | | 85/u5 | | 2y-12x=0 | | 1/5-3=17 | | 1100-550= | | 15x+27y= | | 3cos(x)-5cos(x)=1 | | 3(-4)-2(6)= | | 4q+2(3q-8)=-q-6 | | 3x+3.4=7.3 | | 4x/3=24/5 | | 2+(-9)=x | | 10+h=1 | | -5n-(2n-4)=-2n-9 | | 4(3)+3(4)=19 | | (8-4)-4*2+1= | | 8x+19=5x+76 | | 8k-6(1+k)=5 | | 8x-12y=0 | | 4(1)+3(4)=19 | | 4(-7a+2)+10=-6+8a | | 4(n+1)=(11-n) | | 6*8-(3-7)+8*3= | | w^2=54 | | 4(6)+(-6)=-24 | | inx=-3 | | 7=w+7/7+4w-3/5 | | a(6)-2(-6)=-12 | | 9=5n-1 | | 3-2x=4x+1 |